2014
DOI: 10.1016/j.febslet.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A regulates deoxycytidine kinase activity via Ser‐74 dephosphorylation

Abstract: Edited by Zhijie Chang Keywords:Deoxycytidine kinase Nucleoside analog Ser-74 phosphorylation Protein phosphatase Ser/Thr protein phosphatase 2A a b s t r a c t Deoxycytidine kinase (dCK) is a critical enzyme for activation of anticancer nucleoside analogs. Its activity is controlled via Ser-74 phosphorylation. Here, we investigated which Ser/Thr phosphatase dephosphorylates Ser-74. In cells, the PP1/PP2A inhibitor okadaic acid increased both dCK activity and Ser-74 phosphorylation at concentrations reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…These data are in line with our observations of reduced dCK phosphorylation/activation in the clofarabine resistant p.R183W Aα expressing cells. dCK is activated by phosphorylation on Ser74, a site reported to be dephosphorylated by PP2A [31,37]. Accordingly, we showed that combination of OA with clofarabine was able to reactivate dCK and sensitize the cells to clofarabine, with the most pronounced effect on the p.R183W Aα expressing cells, and thus, suggesting that an unexpected PP2A gain-of-function was responsible for the observed phenotype in these cells.…”
Section: Discussionmentioning
confidence: 60%
“…These data are in line with our observations of reduced dCK phosphorylation/activation in the clofarabine resistant p.R183W Aα expressing cells. dCK is activated by phosphorylation on Ser74, a site reported to be dephosphorylated by PP2A [31,37]. Accordingly, we showed that combination of OA with clofarabine was able to reactivate dCK and sensitize the cells to clofarabine, with the most pronounced effect on the p.R183W Aα expressing cells, and thus, suggesting that an unexpected PP2A gain-of-function was responsible for the observed phenotype in these cells.…”
Section: Discussionmentioning
confidence: 60%
“…27,40 dCK phosphorylation at serine 74 is reversed by protein phosphatase 2A, which negatively regulates dCK activity. 41 Moreover, using a mass spectrometry technique, dCK was found to exist in a complex that contains cyclin-dependent kinase 1 (Cdk1). After IR, Cdk1 interacts with dCK, and the activity of Ckd1 is inhibited by dCK both in vitro and in vivo, making dCK an important G2/M checkpoint regulator in response to DNA damage.…”
Section: Stimulates Ros Generation In Pancreatic Cancer Cells Resultingmentioning
confidence: 99%
“…dCK activation shifts dCK substrate specificity towards deoxycytidine, increases the intracellular dCTP pools and DNA repair activity, and contributes to chemotherapy and radiotherapy resistance . dCK phosphorylation at serine 74 is reversed by protein phosphatase 2A, which negatively regulates dCK activity . Moreover, using a mass spectrometry technique, dCK was found to exist in a complex that contains cyclin‐dependent kinase 1 (Cdk1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, using gemcitabine treatment in tumours of different origin such as pancreas and lung, it was shown that resistance only is predicted by dCK activity and protein level, and not by dCK mRNA level [ 28 ], in agreement with our data. DCK enzymatic activity is controlled by phosphorylation at Ser-74 [ 29 ], and dephosphorylation decreases enzyme activity [ 30 ]. A more active mutant of dCK, with a 10,000-fold increased sensitivity to nucleoside analogues has been created and could be of interest for suicide gene approaches [ 10 , 31 ].…”
Section: Discussionmentioning
confidence: 99%